Volatile organic compound emissions in relation to plant carbon fixation and the terrestrial carbon budget - Kesselmeier, Jürgen; Ciccioli, Paolo; Kuhn, Uwe; Stefani, Paolo; Biesenthal, Thomas; Rottenberger, Stefanie; Wolf, Annette; Vitullo, Marina; Valentini, Ricardo; Nobre, Antonio; Kabat, Pavel; Andreae, Meinrat O. (Global Biogeochemical Cycles, 2002)
A substantial amount of carbon is emitted by terrestrial vegetation as biogenic volatile organic compounds (VOC), which contributes to the oxidative capacity of the atmosphere, to particle production and to the carbon cycle. With regard to the carbon budget of the terrestrial biosphere, a release of these carbon compounds is regarded as a loss of photosynthetically fixed carbon. The significance of this loss for the regional and global carbon cycles is controversial. We estimate the amount of VOC carbon emitted in relation to the CO2 taken up, based on our own enclosure and micrometeorological flux measurements of VOC emissions and CO2 exchange within the Mediterranean area and the tropical rainforest in Amazonia and on literature data. While VOC flux estimates are small in relation to net primary productivity and gross primary productivity, the amount of carbon lost as VOC emissions can be highly significant relative to net ecosystem productivity. In fact, VOC losses are of the same order of magnitude as net biome productivity. Although we must assume that large amounts of these reemissions are recycled within the biosphere, a substantial part can be assumed to be lost into longer-lived oxidation products that are lost from the terrestrial biosphere by transport. However, our current knowledge does not allow a reliable estimation of this carbon loss.
Keywords: carbon cycle; volatile organic compounds (VOC)